The economics of meaningful work: A scoping review - Martijn Hendriks; Femke Cnossen (Global Labor Organization (GLO), 2025)
Meaningful work plays a central role in many people's lives, and the topic attracts interest across a range of social science disciplines. What is the economists' view on meaningful work? This chapter presents a scoping review on the economics of meaningful work. We identified 43 relevant English-language articles in top-quartile economics journals through a systematic search in EconLit and citation tracking. We synthesize how these studies conceptualize, perceive, and operationalize meaningful work, along with their insights into individuals' preferences for meaningful work, how meaningful people consider their work to be, the antecedents and outcomes of meaningful work, and the broader conclusions, implications, and recommendations.
Keywords: J22; J24; J28; J31; J81; 330; Purpose; bullshit jobs; useful job; meaning at work; task significance; literature review